Setting standards for evaluation and testing - Mansfield-Devine, Steve (Biometric technology today, 2014)
Biometric solutions, in the form of fingerprint matching, may have been with us for more than a century, but the industry is still young and – it could be argued – one sign of its immaturity is a lack of standards. It's not that standards don't exist, but that they are missing or inadequate in some critical areas. And one clear example of that is the difficulty organisations face when they are attempting to test, evaluate and compare various vendors’ solutions.